(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
n the article, are presented m ain scientific approaches t o the problems of game modeling, the characteristics of the game are presented, on the basis of the implementation of the game modeling. The role of the game model in the preparation of students until May of professional and pedagogical activity was assigned. The necessity of introduction of interactive technologies into the educational process is substantiated, attention is focused on the technologies of gaming modeling while organizing the educational process in the institution of higher education.